Applied Anthropology: Disciplinary Oxymoron? - Darnell, Regna (Anthropologica, 2015)
This essay argues that the term applied anthropology is an unnecessary oxymoron because the discipline of anthropology itself entails application of anthropological knowledge. Examples from the author's personal experience are used to argue for the application of anthropology as a process of seeing in a particular way, rather than as a mechanical expectation of particular changes embedded in research design. Collaboration of anthropologists with individual consultants and their communities is long established at the centre of applied anthropology. The Canadian Anthropology Society/Société canadienne d'anthropologie (CASCA), in part through its recognition of the significant applied work of Sally Weaver and Marc-Adélard Tremblay, privileges an anthropology of application through dialogue and based in a relational ontology.